2014
DOI: 10.3390/nano4020508
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes and Chronic Granulomatous Disease

Abstract: Use of nanomaterials in manufactured consumer products is a rapidly expanding industry and potential toxicities are just beginning to be explored. Combustion-generated multiwall carbon nanotubes (MWCNT) or nanoparticles are ubiquitous in non-manufacturing environments and detectable in vapors from diesel fuel, methane, propane, and natural gas. In experimental animal models, carbon nanotubes have been shown to induce granulomas or other inflammatory changes. Evidence suggesting potential involvement of carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…3). Other studies have documented granuloma formation after MWCNT exposure [46, 20, 29, 3234]. Granulomas centrally consist of epithelioid and multinucleated giant macrophages surrounded by activated lymphocytes, typically activated CD4+ T cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…3). Other studies have documented granuloma formation after MWCNT exposure [46, 20, 29, 3234]. Granulomas centrally consist of epithelioid and multinucleated giant macrophages surrounded by activated lymphocytes, typically activated CD4+ T cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, nanomaterials like CNTs could interact with immune cells such as platelets, neutrophils, and macrophages. This may lead to the generation of numerous cytokines like interleukins and tumor necrosis factor‐α that are capable of further initiating a series of immune reactions and eventually fibrosis and bronchial granulomas . Alternatively, NPs including SiO 2 , TiO 2 , and hydroxyapatite were capable of increasing cell contractility via massive disruption of the intracellular microtubule assembly without any apparent cytotoxicity, finally resulting in the promotion of strong substrate adhesions and limit of cell motility .…”
Section: Recent Discoveries In Nanotoxicology and Nanomedical Implicamentioning
confidence: 99%
“…The biocompatibility is the first and foremost consideration for most applications. Carbon nanotube research has demonstrated that free nano‐dimensional carbon‐based particles can interfere with the metabolism and membrane integrity of cells, leading to potential toxic effects . In addition, if there is degradation of the material, or any mechanism by which nanomaterials can enter the blood stream, the effects of the particles on tissues, such as lungs, liver, and kidneys, and the ability of the body to excrete the materials needs to be considered.…”
Section: Graphene For Tissue Engineeringmentioning
confidence: 99%